High-temperature-resistant magnetic liquid metal coupling material as well as preparation method and application thereof
By using high-temperature resistant magnetic liquid metal coupling materials, the problem that traditional ultrasonic coupling agents cannot work effectively in high-temperature environments is solved, and high-precision ultrasonic coupling and bolt stress monitoring are achieved, ensuring the safe and stable operation of oil production bolts.
Patent Information
- Application Number
- CN202411680647.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-25
AI Technical Summary
In high temperature environments, traditional ultrasonic coupling agents cannot meet the demand for stress monitoring of oil production bolts, resulting in low detection accuracy and poor coupling effect, affecting the health status monitoring of bolts.
High temperature resistant magnetic liquid metal coupling material is used, which consists of InGaSn liquid metal matrix, CoFeNiCr high-entropy magnetic particle filler and CaF-BaF low-surface energy material. Through specific preparation methods and combined proportions, an efficient ultrasonic coupling material is formed.
High-precision ultrasonic coupling in high-temperature environments is achieved, the accuracy and reliability of bolt stress monitoring is improved, the service life of coupling materials is extended, and the safety and stability of oil production bolts are ensured.
Smart Images

Figure CN119506676A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of high-temperature coupling agents, and in particular to a high-temperature resistant magnetic liquid metal coupling material for oil production bolts, a preparation method and an application thereof. Background Art
[0002] Thermal recovery wellhead devices are the key research direction of heavy oil production equipment manufacturing in oil fields. Safety and reliability are one of the indicators that must be considered in their design and manufacturing. Bolt connection, as an important assembly method in heavy oil thermal recovery wellhead devices and wind turbine assembly, plays the role of pressure sealing, component connection and support fixation. Its selection, strength verification and assembly quality are important guarantees for the reliability of heavy oil thermal recovery wellhead devices and wind turbines. The wellhead steam injection temperature of thermal recovery devices often reaches 400℃. In the long-term high-temperature service environment, the bolts are very likely to lose preload and break, threatening the normal operation of the whole machine. By analyzing past bolt breakage accidents, the failure behavior of high-strength bolts includes the following two situations: one is that the axial force is too large to cause overload breakage; the other is that the initial preload is insufficient, or the preload caused by alternating load is insufficient, causing the bolt to loosen. Therefore, the change in the stress state of the bolt (including axial preload and lateral shear load) is the main cause of bolt loosening and fracture. The fatigue, creep, stress corrosion cracking of the bolt are closely related to stress. The monitoring of the stress state of the bolt has become one of the main contents of safety supervision of large equipment. However, there is a lack of understanding of the evolution mechanism of bolt stress coupled with multiple factors such as stress relaxation and bolt loosening in high temperature environments. There is a serious lack of non-destructive measurement methods for in-service bolt stress, especially a lack of high-precision online stress monitoring methods. It is urgent to develop high-precision and high-reliability stress sensing and monitoring technology for bolts, build online monitoring methods and evaluation technologies with bolt stress as the core indicator, and realize the health status monitoring of bolts throughout their life cycle.
[0003] Ultrasonic axial force measurement technology is based on the principle of acoustic elasticity. The propagation speed of ultrasound in the bolt is related to the bolt stress. By observing the propagation time of ultrasound in the bolt, the propagation speed of ultrasound can be known. The functional relationship between the ultrasonic propagation time and the axial stress of the bolt can be established, and the correlation coefficient between the load value and the flight time in the functional relationship can be obtained through calibration tests. The flight time of ultrasound in the bolt under different loads can be measured to quantitatively measure the load value borne by the bolt, thereby judging the health of the bolt connection. The ultrasonic method for measuring stress has the advantages of strong penetration ability, fast speed, low cost, no damage to the test piece, and wide application range. It has been widely used in the field of stress measurement.
[0004] When ultrasonic sensors are used to detect bolt stress, ultrasonic coupling agents are required to couple ultrasound into the bolts. Traditional coupling agents used at room temperature are widely used, but they cannot withstand high temperatures above 100°C. The temperature of oil production bolts can reach 400°C, and traditional ultrasonic coupling agents cannot meet the use requirements. For ultrasonic flaw detection and ultrasonic thickness measurement under high temperature conditions, good coupling between the probe and the workpiece is the most important condition. Especially in high temperature detection, the detection time is very short, and a good coupling effect is required. When the coupling quality changes, the sound energy penetrating the workpiece will also change, and thus the sound pressure at a certain depth in the workpiece will also change. Therefore, the use of high temperature coupling agents can achieve a good coupling effect, reduce clutter interference, and improve the accuracy of judgment. However, traditional high temperature coupling agents cannot be used for a long time, and are prone to solidification and loss of coupling effect, which seriously affects the detection of oil production bolt stress. For this reason, it is necessary to develop high temperature coupling materials that can withstand high temperatures and can be coupled. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a high temperature resistant magnetic liquid metal coupling material and a preparation method and application thereof. The present invention makes full use of the performance advantages of liquid metal, high entropy material and low surface energy material to prepare a high temperature coupling material, providing a new idea for the research and development of new coupling agents.
[0006] In a first aspect, the present invention provides a high temperature resistant magnetic liquid metal coupling material, which is realized by adopting the following technical solution.
[0007] A high temperature resistant magnetic liquid metal coupling material comprises a liquid metal matrix, a high entropy magnetic particle filler and a low surface energy material; the liquid metal matrix is an InGaSn alloy, the high entropy magnetic particle filler is CoFeNiCr, and the low surface energy material is a CaF-BaF mixture.
[0008] Furthermore, the crystal structure of the liquid metal matrix is a hexagonal crystal structure; the contents of the three elements in the InGaSn alloy are In: 10-25 at.%, Ga: 60-80 at.%, and Sn: 15-30 at.%.
[0009] Furthermore, the crystal structure of the high entropy magnetic particle filler is a face-centered cubic metal; the contents of the four elements in CoFeNiCr are Co: 20-30at.%, Fe: 25-30at.%, Ni: 25-35at.%, and Cr: 20-25at.%.
[0010] Furthermore, the CaF content in the low surface energy material is 50-60 at.%, and the BaF content is 40-50 at.%. The particle diameter of the low surface energy material is 10-30 microns.
[0011] Furthermore, in the high temperature resistant magnetic liquid metal coupling material, the mass ratio of the CoFeNiCr-CaF-BaF mixed powder is 25-35wt.%, and the mass ratio of the InGaSn liquid metal is 65-75wt.%; the mass ratio of CoFeNiCr in the CoFeNiCr-CaF-BaF mixed powder is 70-80wt.%, and the mass ratio of CaF-BaF is 20-30wt.%.
[0012] In a second aspect, the present invention provides a method for preparing a high temperature resistant magnetic liquid metal coupling material, which is achieved by adopting the following technical solution.
[0013] A method for preparing the above-mentioned high temperature resistant magnetic liquid metal coupling material comprises the following steps:
[0014] S1. Mix the In, Ga and Sn alloy materials and stir and dissolve them at a temperature range of 100-200°C;
[0015] S2. The Co, Fe, Ni, and Cr metal powders are mixed and then ball-milled in a ball mill. The powder diameter after ball milling is controlled to be 0.5-20 microns;
[0016] S3. Mix CaF and BaF and stir for 10-20 min by mechanical stirring;
[0017] S4. The CoFeNiCr high entropy alloy powder is mixed with CaF and BaF and stirred for 10-20 min by mechanical stirring;
[0018] S5. Add the CoFeNiCr-CaF-BaF mixed powder into the liquid metal matrix InGaSn, heat it for stabilization treatment, and obtain a high temperature resistant magnetic liquid metal coupling material after the heat preservation treatment.
[0019] Furthermore, in step S1, the stirring time is 60-120 min.
[0020] Furthermore, in step S5, the stabilization treatment temperature is 250-400° C., and the insulation time is 60-120 min.
[0021] In a third aspect, the present invention provides a use of a high temperature resistant magnetic liquid metal coupling material, which is achieved by adopting the following technical solution.
[0022] An application of the above-mentioned high-temperature resistant magnetic liquid metal coupling material in oil production bolt stress monitoring.
[0023] This application has the following beneficial effects.
[0024] (1) The present invention applies liquid metal to ultrasonic coupling in a high-temperature environment, changing the current situation that there is no coupling agent that can withstand long-term high temperatures, and provides a new idea for the research and development of high-temperature coupling agents;
[0025] (2) The present invention applies magnetic high entropy alloy to high temperature resistant magnetic liquid metal coupling material, which can form a good constraint on the liquid metal. During the detection or monitoring process, the magnetic material and the liquid metal are combined together and will not flow around to affect the ultrasonic coupling effect;
[0026] (3) The application of low surface energy materials in high temperature resistant magnetic liquid metal coupling materials can reduce the surface energy of liquid metal, improve its wettability with the surface of metal bolts, and improve the coupling effect;
[0027] (4) The present invention applies high temperature resistant magnetic liquid metal coupling material to the stress monitoring of oil production bolts, which can monitor the health status of the bolts in real time and has important value in ensuring the safety of oil production bolts. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a schematic structural diagram of the high temperature resistant magnetic liquid metal coupling material of the present invention;
[0029] Figure 2 It is a schematic diagram of high temperature ultrasonic coupling detection of the present invention.
[0030] Among them, 1. liquid metal matrix; 2. CoFeNiCr high entropy magnetic powder; 3. CaF-BaF low surface energy powder; 4. detection line; 5. high temperature curing glue; 6. high temperature magnet; 7. high temperature resistant magnetic liquid metal coupling material; 8. oil production bolt; 9. confinement ring; 10. piezoelectric chip. DETAILED DESCRIPTION
[0031] The present patent application is further described below in conjunction with embodiments.
[0032] Example 1
[0033] A method for preparing a high temperature resistant magnetic liquid metal coupling material comprises the following steps:
[0034] (1) In, Ga, and Sn alloy materials are mixed and fully dissolved at 100°C. Stirring is performed while keeping the temperature for 60 minutes. The ratio of each element is In: 10 at.%; Ga: 60 at.%; Sn: 20 at.%;
[0035] (2) Co, Fe, Ni, and Cr metal powders are mixed and then ball-milled in a ball mill. The contents of the four elements in CoFeNiCr are Co: 20 at.%, Fe: 25 at.%, Ni: 25 at.%, and Cr: 20 at.%. After ball milling, the powder diameter is controlled to be 0.5 μm.
[0036] (3) CaF and BaF were mixed by mechanical stirring for 10 min, wherein the CaF content was 50 at.%, the BaF content was 50 at.%, and the particle diameter was 10 μm;
[0037] (4) CoFeNiCr high entropy alloy powder is mixed with CaF and BaF, wherein the mass ratio of CoFeNiCr is 70wt.%, and the mass ratio of CaF-BaF is 30wt.%, and a mechanical stirring method is used for a stirring time of 10 min;
[0038] (5) Add the CoFeNiCr-CaF-BaF mixed powder into the liquid metal matrix InGaSn, heat it for stabilization treatment, the stabilization treatment temperature is 250°C, and the heat preservation time is 60 minutes. The mass ratio of the CoFeNiCr-CaF-BaF mixed powder is 25wt.%, and the mass ratio of the InGaSn liquid metal is 75wt.%. After the heat preservation treatment, the multi-component magnetic liquid metal coupling material CoFeNiCr-InGaSn-CaF-BaF is prepared.
[0039] Example 2
[0040] A method for preparing a high temperature resistant magnetic liquid metal coupling material comprises the following steps:
[0041] (1) Mix In, Ga, and Sn alloy materials and fully dissolve them at 200°C. Stir while keeping warm for 120 minutes. The ratio of each element is In: 25 at.%, Ga: 60 at.%, and Sn: 15 at.%;
[0042] (2) Co, Fe, Ni, and Cr metal powders are mixed and then ball-milled in a ball mill. The contents of the four elements in CoFeNiCr are Co: 30 at.%, Fe: 25 at.%, Ni: 25 at.%, and Cr: 20 at.%. After ball milling, the powder diameter is controlled to be 20 μm.
[0043] (3) CaF and BaF are mixed by mechanical stirring for 20 min, wherein the CaF content is 60 at.%, the BaF content is 40 at.%, and the particle diameter is 30 μm;
[0044] (4) CoFeNiCr high entropy alloy powder is mixed with CaF and BaF, wherein the mass ratio of CoFeNiCr is 80wt.%, and the mass ratio of CaF-BaF is 20wt.%, and a mechanical stirring method is used for a stirring time of 20min;
[0045] (5) Add the CoFeNiCr-CaF-BaF mixed powder into the liquid metal matrix InGaSn, heat it for stabilization treatment, the stabilization treatment temperature is 400°C, and the heat preservation time is 120 minutes. The mass ratio of the CoFeNiCr-CaF-BaF mixed powder is 35wt.%, and the mass ratio of the InGaSn liquid metal is 65wt.%. After the heat preservation treatment, the multi-component magnetic liquid metal coupling material CoFeNiCr-InGaSn-CaF-BaF is prepared.
[0046] Example 3
[0047] A method for preparing a high temperature resistant magnetic liquid metal coupling material comprises the following steps:
[0048] (1) In, Ga, and Sn alloy materials are mixed and fully dissolved at 150°C. Stirring is performed while keeping the temperature for 100 minutes. The ratio of each element is In: 20 at.%, Ga: 65 at.%, and Sn: 15 at.%.
[0049] (2) Co, Fe, Ni, and Cr metal powders are mixed and then ball-milled in a ball mill. The contents of the four elements in CoFeNiCr are Co: 25 at.%, Fe: 30 at.%, Ni: 25 at.%, and Cr: 20 at.%. After ball milling, the powder diameter is controlled to be 10 μm.
[0050] (3) CaF and BaF were mixed by mechanical stirring for 15 min, wherein the CaF content was 55 at.%, the BaF content was 45 at.%, and the particle diameter was 18 μm;
[0051] (4) CoFeNiCr high entropy alloy powder is mixed with CaF and BaF, wherein the mass ratio of CoFeNiCr is 75wt.%, and the mass ratio of CaF-BaF is 25wt.%, and a mechanical stirring method is used for a stirring time of 20 min;
[0052] (5) Add the CoFeNiCr-CaF-BaF mixed powder into the liquid metal matrix InGaSn, heat it for stabilization treatment, the stabilization treatment temperature is 300°C, and the heat preservation time is 90 minutes. The mass ratio of the CoFeNiCr-CaF-BaF mixed powder is 30wt.%, and the mass ratio of the InGaSn liquid metal is 70wt.%. After the heat preservation treatment, the multi-component magnetic liquid metal coupling material CoFeNiCr-InGaSn-CaF-BaF is prepared.
[0053] Example 4
[0054] A method for preparing a high temperature resistant magnetic liquid metal coupling material comprises the following steps:
[0055] (1) Mix In, Ga, and Sn alloy materials and fully dissolve them at 180°C. Stir while keeping warm for 60 minutes. The ratio of each element is In: 25 at.%, Ga: 60 at.%, and Sn: 15 at.%;
[0056] (2) Co, Fe, Ni, and Cr metal powders are mixed and then ball-milled in a ball mill. The contents of the four elements in CoFeNiCr are Co: 25 at. %; Fe: 25 at. %; Ni: 25 at. %; Cr: 25 at. %; and the powder diameter after ball milling is controlled to be 10 μm;
[0057] (3) CaF and BaF were mixed by mechanical stirring for 15 min, wherein the CaF content was 50 at.%, the BaF content was 50 at.%, and the particle diameter was 20 μm;
[0058] (4) CoFeNiCr high entropy alloy powder is mixed with CaF and BaF, wherein the mass ratio of CoFeNiCr is 78wt.%, and the mass ratio of CaF-BaF is 22wt.%, and a mechanical stirring method is used for a stirring time of 15 min;
[0059] (5) Add the CoFeNiCr-CaF-BaF mixed powder into the liquid metal matrix InGaSn, heat it for stabilization treatment, the stabilization treatment temperature is 300°C, and the heat preservation time is 80 minutes. The mass ratio of the CoFeNiCr-CaF-BaF mixed powder is 32wt.%, and the mass ratio of the InGaSn liquid metal is 68wt.%. After the heat preservation treatment, the multi-component magnetic liquid metal coupling material CoFeNiCr-InGaSn-CaF-BaF is prepared.
[0060] Example 5
[0061] A method for preparing a high temperature resistant magnetic liquid metal coupling material comprises the following steps:
[0062] (1) In, Ga, and Sn alloy materials are mixed and fully dissolved at a temperature range of 150°C. Stirring is performed while keeping the temperature for 80 minutes. The ratio of each element is In: 10 at.%; Ga: 70 at.%; Sn: 20 at.%;
[0063] (2) Co, Fe, Ni, and Cr metal powders are mixed and then ball-milled in a ball mill. The contents of the four elements in CoFeNiCr are Co: 25 at.%, Fe: 30 at.%, Ni: 20 at.%, and Cr: 25 at.%. After ball milling, the powder diameter is controlled to be 8 μm.
[0064] (3) CaF and BaF were mixed by mechanical stirring for 15 min, wherein the CaF content was 55 at.%, the BaF content was 45 at.%, and the particle diameter was 25 μm;
[0065] (4) CoFeNiCr high entropy alloy powder is mixed with CaF and BaF, wherein the mass ratio of CoFeNiCr is 79wt.%, and the mass ratio of CaF-BaF is 21wt.%, and a mechanical stirring method is used for a stirring time of 15 min;
[0066] (5) Add the CoFeNiCr-CaF-BaF mixed powder into the liquid metal matrix InGaSn, heat it for stabilization treatment, the stabilization treatment temperature is 300°C, and the heat preservation time is 80 minutes. The mass ratio of the CoFeNiCr-CaF-BaF mixed powder is 34wt.%, and the mass ratio of the InGaSn liquid metal is 66wt.%. After the heat preservation treatment, the multi-component magnetic liquid metal coupling material CoFeNiCr-InGaSn-CaF-BaF is prepared.
[0067] Performance Testing
[0068] The ultrasonic attenuation rates of the coupling materials prepared in Examples 1-5 were measured (referring to JIS Z 2354:2012: Test method for measuring ultrasonic attenuation coefficient of solids). The experimental results are shown in Table 1.
[0069] Table 1 Ultrasonic attenuation rate measurement of high temperature magnetic liquid metal coupling materials
[0070] Coupling material series 100℃ 200℃ 300℃ 400℃ Example 1 5% 10% 14% 15% Example 2 20% 24% 26% 28% Example 3 14% 19% 21% 22% Example 4 19% 22% 25% 26% Example 5 25% 30% 33% 35%
[0071] Note: Ultrasonic attenuation rate = (ultrasonic incident intensity - ultrasonic reflection intensity) / ultrasonic incident intensity
[0072] Application Examples
[0073] like Figure 2 As shown, there is a restriction ring 9 on the surface of the oil production bolt 8, and the main purpose of the restriction ring 9 is to limit the flow of the high temperature resistant magnetic liquid metal coupling material 7; there is a piezoelectric chip 10 on the high temperature resistant magnetic liquid metal coupling material 7, and the purpose of the piezoelectric chip 10 is to excite ultrasonic waves. The piezoelectric chip 10 is fixed by a high temperature curing glue 5, and there is a high temperature magnet 6 on the piezoelectric chip 10. The function of the high temperature magnet 6 is to generate a strong magnetic force during detection, adsorb the ultrasonic probe on the surface of the bolt, and at the same time play a restraining role on the high temperature resistant magnetic liquid metal coupling material 7. Through the above design, the high temperature resistant magnetic liquid metal coupling material can play a good coupling role and meet the functional requirements of ultrasonic coupling into the bolt.
[0074] The embodiments of this specific implementation method are all preferred embodiments of the present invention, and are not intended to limit the protection scope of the present invention. Therefore, any equivalent changes made based on the structure, shape, and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A high temperature resistant magnetic liquid metal coupling material, characterized in that: It includes a liquid metal matrix, a high-entropy magnetic particle filler, and a low-surface energy material; the liquid metal matrix is an InGaSn alloy, the high-entropy magnetic particle filler is CoFeNiCr, and the low-surface energy material is a CaF-BaF mixture.
2. The high temperature resistant magnetic liquid metal coupling material according to claim 1, characterized in that: The crystal structure of the liquid metal matrix is a hexagonal crystal structure; the contents of the three elements in the InGaSn alloy are In: 10-25 at.%, Ga: 60-80 at.%, and Sn: 15-30 at.%.
3. The high temperature resistant magnetic liquid metal coupling material according to claim 1, characterized in that: The crystal structure of the high entropy magnetic particle filler is face-centered cubic metal; the contents of the four elements in CoFeNiCr are Co: 20-30at.%, Fe: 25-30at.%, Ni: 25-35at.%, and Cr: 20-25at.%.
4. The high temperature resistant magnetic liquid metal coupling material according to claim 1, characterized in that: The CaF content in the low surface energy material is 50-60 at.%, and the BaF content is 40-50 at.%. The particle diameter of the low surface energy material is 10-30 microns.
5. The high temperature resistant magnetic liquid metal coupling material according to claim 1, characterized in that: In the high temperature resistant magnetic liquid metal coupling material, the mass ratio of CoFeNiCr-CaF-BaF mixed powder is 25-35wt.%, and the mass ratio of InGaSn liquid metal is 65-75wt.%; the mass ratio of CoFeNiCr in the CoFeNiCr-CaF-BaF mixed powder is 70-80wt.%, and the mass ratio of CaF-BaF is 20-30wt.%.
6. A method for preparing the high temperature resistant magnetic liquid metal coupling material according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. Mix the In, Ga and Sn alloy materials and stir and dissolve them at a temperature range of 100-200°C; S2. The Co, Fe, Ni, and Cr metal powders are mixed and then ball-milled in a ball mill. The powder diameter after ball milling is controlled to be 0.5-20 microns; S3. Mix CaF and BaF and stir for 10-20 min by mechanical stirring; S4. The CoFeNiCr high entropy alloy powder is mixed with CaF and BaF and stirred for 10-20 min by mechanical stirring; S5. Add the CoFeNiCr-CaF-BaF mixed powder into the liquid metal matrix InGaSn, heat it for stabilization treatment, and obtain a high temperature resistant magnetic liquid metal coupling material after the heat preservation treatment.
7. The method for preparing a high temperature resistant magnetic liquid metal coupling material according to claim 6, characterized in that: In step S1, the stirring time is 60-120 min.
8. The method for preparing a high temperature resistant magnetic liquid metal coupling material according to claim 6, characterized in that: In step S5, the stabilization treatment temperature is 250-400° C., and the insulation time is 60-120 min.
9. Use of the high temperature resistant magnetic liquid metal coupling material according to any one of claims 1 to 5 in stress monitoring of oil production bolts.